Enhancing students' conceptual understanding of trigonometric functions through geogebra-based learning - Juandi, Juandi; Sugiatno, Sugiatno; Noviani, Evi (Universitas Islam Raden Intan Lampung, INDONESIA, 2025)
Purpose: This study explores how students construct basic trigonometric function definitions using GeoGebra, examines their engagement, and identifies the challenges they face. The research follows a constructivist approach, emphasizing active learning through technology to improve students’ understanding of mathematical concepts.Method: A pedagogical action research method was used, involving four stages: observation, planning, action, and reflection. The study was conducted with 31 Grade X science students from SMA Negeri 1 Sungai Kakap, selected through purposive sampling. Data were collected through observations, questionnaires, and interviews to assess the effectiveness of the GeoGebra-based learning approach.Findings: The results show that students successfully built definitions of basic trigonometric functions, achieving an average score of 95.24 percent, classified as